2006
DOI: 10.1074/mcp.r600004-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Urinary Biomarkers

Abstract: A myriad of proteins and peptides can be identified in normal human urine. These are derived from a variety of sources including glomerular filtration of blood plasma, cell sloughing, apoptosis, proteolytic cleavage of cell surface glycosylphosphatidylinositol-linked proteins, and secretion of exosomes by epithelial cells. Mass spectrometry-based approaches to urinary protein and peptide profiling can, in principle, reveal changes in excretion rates of specific proteins/peptides that can have predictive value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
321
0
9

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(332 citation statements)
references
References 77 publications
2
321
0
9
Order By: Relevance
“…Urinary proteins originate from different sites, e.g. from plasma via glomerular filtration, from renal tubular epithelial cells, from shedding of whole cells or membrane fragments along the tubulus and bladder or from exosome secretion [30,34]. According to recent recommendations for urinary proteomics [33], we collected second morning urine samples and added sodium azide instantly to minimise contamination of proteins from bacteria [3], which can change the urinary proteome profile [33].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary proteins originate from different sites, e.g. from plasma via glomerular filtration, from renal tubular epithelial cells, from shedding of whole cells or membrane fragments along the tubulus and bladder or from exosome secretion [30,34]. According to recent recommendations for urinary proteomics [33], we collected second morning urine samples and added sodium azide instantly to minimise contamination of proteins from bacteria [3], which can change the urinary proteome profile [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhou et al [9] determined that the sediment phase of urine accounts for approximately 50% of the total protein content by mass and is primarily comprised of uromodulin. Thus, as a simple prefractionation technique, removal of the sediment phase can be considered beneficial for the analysis of low-abundant protein components in urine supernatants [12]. However, Zhou et al clearly demonstrated (through SDS-PAGE images) that several other proteins contribute to the sediment phase of urine; a comprehensive study to identify these proteins has yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…High molecular weight proteins (albumin, for example) are able to pass through the glomerular filtrate. Small proteins, or peptides (< 10 kDa) are easily filtered by the glomerulus and constitute an important source of information, even if the peptide is the result of proteolysis of larger proteins circulating in plasma (1)(2)(3). Urine is especially attractive for biomarker discovery in urological diseases since any change in concentration of proteins in plasma will reflect in the urine.…”
Section: Introductionmentioning
confidence: 99%